The making of iranianness in the kitchen: a textual analysis of the cooking game show befarmaeed sham - Alireza Azeri Matin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The emergence and rapid proliferation of the predominantly anti-regime Farsi satellite TV channels (FSTCs) and their productions since early 1990s have not only transformed the Iranian mediascape, but also challenged the state’s definition of Iranianness. Among the new generations of these free-to-air transnational channels, is MANOTO, a London-based television network which became a familiar name among Iranians since 2010 after premiering Befarmaeed Sham, a cooking game show copied from the successful British TV show Come and Dine with Me. Being broadcast for more than a decade, this reality show depicts the lives of ordinary Iranians in diaspora who have to deal with the unaccustomed culture of the West. Since FSTCs are strictly regarded by Iranian authorities as means of cultural invasion, the representations in Befarmaeed Sham are naturally seen to be in contrast with the Islamic regime’s views on what it means to be Iranian. Yet, what remains less known is how this new form of popular cultural programme redefines Iranianness. Therefore, by performing a series of textual analyses on 7 sequences selected from various episodes of Befarmaeed Sham, and with a focus on the contestants’ utterances, the present study uncovers some of the key representational aspects of this reality show. Ultimately, while highlighting the subtleties in cultural representation that render Befarmaeed Sham political, it is argued that this television programme offers audiences a new space for rethinking their Iranian selves.